Accounting for the impact of variety-seeking: Theory and application to HSR-air intermodality in China. (June 2018) - Song, Fangqing; Hess, Stephane; Dekker, Thijs
Abstract: While variety-seeking has been analysed intensively in consumer marketing, little is known about its impact in the transport world where many novel travel services have emerged in recent years. In this paper, we investigate how variety-seeking could influence intercity travellers' mode choice decisions in the new context of HSR (high-speed rail)-air intermodality in China. The study is based on data collected in Shanghai, including responses to stated choice tasks and attitudinal statements on variety-seeking. An integrated choice and latent variable (ICLV) model is proposed with a view to provide us with a more behaviourally realistic explanation of respondents' choice decisions. The research findings suggest that variety-seeking has different impacts across modes, where variety seekers would be more likely to choose the newly-introduced integrated HSR-air option whereas variety avoiders have a higher propensity to choose car-air or traditional separate HSR-air alternative. Meanwhile, this study also examines the impact of various level-of-service attributes in mode choice behaviour, with results implying that long layover would heavily impair the attractiveness of integrated HSR-air service, and integrated luggage handling service is favourable to attract intermodal passengers while the effect of integrated ticketing system remains ambiguous. Highlights: Variety-seeking tendency varies across respondents. Variety seekers tend to choose the new integrated HSR-air service. Younger and lower-income people show stronger variety-seeking tendencies. Connection time is highly valued by passengers. Luggage integration is favourable to travellers with more luggage.